Kesukaran Pelajar Berinteraksid Engan Al-Ma Ajim al Arabiyyah Dan Cara-Cara Mengatasinya: Satu Kajian Di Institusi Pengajian Tinggi Awam (Kolej Universiti Islam Malaysia, Universiti Kebangsaan Malaysia Dan Universiti Islam Antarabangsa Malaysia) - Wan Moharani Mohammad; Radziah Ismail; Nazipah Mat Shaid @ Md. Said; Badrul Munir Muhamad Nur; Nabilah Yusof; Afizzjah Artini Jusoh (Universiti Sains Islam Malaysia, 2024)
The usage of Arabic dictionary in the process of learning Arabic is essential. However it is observed that students in Public Higher Lear~iing Institution in Malaysia who study Arabic are facing difficulty in using Arabic dictionary. Therefore a study entitled "The difficulty in using Arabic dictionary and its solution: a study among Public Higher Learning Institution's students (KUIM, UKM and UIAM) was conducted, to recognize the problem and offer the solution. This is both a library and field research. It is found that the problem arose from the inadequate knowledge among the students regarding Arabic dictionary, Arabic morphology (sarf) and the altitude of certain students especially those who neglected the practice of Arabic dictionary. It is recommended that the students should be provided with the knowledge and positive altitude towards the usage of Arabic dictionary.